Experience of Officials in Improving the Performance of Dengue Fever Surveillance in Pidie Regency a Qualitative Study - Ansarullah Ansarullah; M. Marthoenis; T. Maulana; Nasrul Zaman; Said Usman (International Journal of Public Health, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern in Pidie Regency, Indonesia. Although digital surveillance systems such as SKDR have been introduced, the effectiveness of dengue control still largely depends on the role and capacity of surveillance officers. This study aimed to explore the experiences of dengue surveillance personnel in Pidie Regency, focusing on their knowledge, reporting mechanisms, encountered challenges, and expectations regarding the surveillance system. A qualitative method with a phenomenological design was employed, involving 11 purposively selected informants. Data were gathered through in-depth interviews and analyzed using the Miles and Huberman framework, encompassing data reduction, data display, and conclusion drawing. The analysis revealed six main themes: officers' knowledge and understanding of dengue, sources of data and case collection methods, the use of digital applications for reporting and analysis, implementation challenges in the field, cross-sectoral roles and support from village governments, and officers' expectations for improvement. The findings highlight that limited resources, technical issues, and insufficient intersectoral collaboration hinder effective surveillance. Strengthening the surveillance system requires responsive strategies that consider on-the-ground challenges. A deeper understanding of surveillance officers’ field experiences is crucial for developing adaptive and sustainable public health interventions for dengue control.